Root coverage using modified tunneling technique with acellular dermal matrix for treatment of gingival recession associated with orthodontic treatment: A case report - Rosa Pratiwi; Irma Dewi Ratnawati; Agung Krismariono (Faculty of Dentistry, Universitas Islam Sultan Agung, 2023)
Background: Gingival recession has a number of causes, including orthodontic therapy. The degree and extent of gingival recession and orthodontic therapy are strongly correlated. Care must be taken in choosing the best soft tissue grafting technique. Development of a number of new and improved surgical techniques, including the modified tunneling technique. Case Management: A-24-year-old female patient came to Periodontic Clinic Dental Hospital of Airlangga University with a chief complain of gingival recession in mandibular central incisors since 6 months ago. The patient complained about dental sensitivity. The dental history revealed that she had undergone fixed orthodontic therapy for 7 years. She revealed the fixed orthodontic appliance was put off since 8 months ago. The patient concern about her appearance and aesthetic problem. Gingival recession on buccal surface tooth 31 and 41 extending 1,5-2 mm apical of the incisors was found in clinical assessment. This case classified as Miller class III. The doctor planned root coverage procedure using modified tunnel technique. Acellular dermal matrix (SuredermÂ®) was chosen as a gingival graft. Discussion: Creating a